Recovery When Doing Physical Activity in Futsal Athletes (Department of Physical Education, Sport, Health and Recreation, 2023)
The purpose of this research is to restore the athlete's physical condition as soon as possible after doing sports activities. This is a Quantitative research, which is a research model that emphasizes the analysis of numerical data (numbers) that are processed using statistical methods in each result obtained. Based on the results that have been done, it shows that there is a significant difference between the pretest and posttest in the physical activity of the active group and the passive group. The description value of the average active pretest is 47.00 to 57.14 in the posttest and the sig.0.00 value <0.05. The mean value of the passive group pretest is 40.25 to 52.50 in the posttest and the sig. 0.28 < 0.05. Normality test value of 0.200 > 0.05, so it can be concluded that the active group and passive group data are normally distributed. Sig value, 0.30 > 0.05, it can be concluded that the physical activity testing of the active group and passive group of futsal athletes is homogeneous. The sig value of the active T test is 0.00 <0.05 which means that Ho is rejected, and the passive value is 0.28 which means Ho is accepted. Thus it can be concluded that there is an influence on recovery when doing physical activity in athletes.